Pregnancy : risk factors, management and recovery - Altamirano Frias, Teresa; Jaquez Cano, Miguel (Obstetrics and gynecology advances., 2012)
In this book, the authors present current research in the study of the risk factors, management and recovery process in pregnancy. Topics include glaucoma management during pregnancy; thyroid dysfunction and management during pregnancy; the safety and administration of medical treatment for ENT diseases in pregnant women; azoospermia, cryopreservation and successful pregnancy; pregnancy and cultural knowledge and practices among Northern Thai women; endothelium-derived hyperpolarising factor and pregnancy; and, asthma management during pregnancy and laparoscopic appendectomy during pregnancy.